Evaluating the Efficacy of Two Regional Pain Management Modalities in Autologous Breast Reconstruction. Issue 1 (19th January 2022) - Rendon, Juan L.; Borrell-Vega, Jaume; Reyes, Joshua-Paolo C.; Wang, Diana M.; Roeth, Cory; Abdel-Rasoul, Mahmoud; Skoracki, Roman J.; Harter, Ronald L.; Moffatt-Bruce, Susan D.; Humeidan, Michelle L.
Abstract : Background: At our institution, multimodal opiate-sparing pain management is the cornerstone of our enhanced recovery program for autologous breast reconstruction. The purpose of this study was to compare postoperative outcomes and pain control metrics following implementation of an enhanced recovery program with two different regional analgesia approaches. Methods: This retrospective cohort study identified 145 women who underwent autologous breast reconstruction from 2015 to 2017. Three groups were included: historical control patients (n = 46) and enhanced recovery patients that received multimodal pain management including a postoperative transversalis abdominis plane block with either a continuous local anesthetic catheter (n = 60) or a single-shot of liposomal bupivacaine (n = 39). The primary outcome was pain scores in the first three postoperative days. Secondary outcomes were opioid consumption in oral morphine equivalents and length of stay. Results: Postoperative pain scores were similar across all three groups until postoperative day 3. Length of stay was significantly shorter in both of the enhanced recovery cohorts (3.0 [3.0, 4.0]) compared with control patients (4.0 [4.0, 5.0], P < 0.001). Likewise, average total oral morphine equivalents consumption was significantly reduced in enhanced recovery patients (continuous catheter 215.9 (95% CI, 165.4–266.3); liposomal bupivacaine 211.0 (95% CI, 154.8–267.2); control 518.4 (95% CI 454.2–582.7), P < 0.001). Neither length of stay ( P = 0.953), nor oral morphine equivalents consumption ( P = 0.883) differed by type of regional analgesia. Conclusion: Compared with control patients, both approaches to regional transversalis abdominis plane block analgesia as part of an opiate-sparing enhanced recovery pain management strategy were successful, but neither superior to the other.